Development of Subcarangiform Bionic Robotic Fish Propelled by Shape Memory Alloy Actuators - Muralidharan, M.; Palani, I.A. (Defence Science Journal, 2021)
In this paper, a shape memory alloy (SMA) actuated subcarangiform robotic fish has been demonstrated using a spring based propulsion mechanism. The bionic robotic fish developed using SMA spring actuators and light weight 3D printed components can be employed for under water applications. The proposed SMA spring-based design without conventional motor and other rotary actuators was able to achieve two-way shape memory effect and has reproduced the subcarangiform locomotion pattern. The positional kinematic model has been developed and the dynamics of the proposed mechanism were analysed and simulated using Automated Dynamic Analysis of Mechanical Systems (ADAMS). An open loop Arduino-relay based switching control has been adopted to control the periodic actuation of the SMA spring mechanism. The undulation of caudal fin in air and water medium has been analysed. The caudal fin and posterior body of the developed fish prototype have taken part in undulation resembling subcarangiform locomotion pattern and steady swimming was achieved in water with a forward velocity of 24.5 mm/s. The proposed design is scalable, light weight and cost effective which may be suitable for underwater surveillance application.